NADH supplementation improves human oocyte maturation and developmental competence of resulting embryos in controlled ovarian hyperstimulation cycles: a pilot study implicating the CDK2/GAS6 signaling pathway - Zhang, Qiqi; Yang, Han; Yang, Dandan; Lu, Hedong; Xiong, Min; Xie, Lanxin; Fan, Yongqi; Zhang, Kuanjian; Zhang, Chao; Ye, Tingting; Ding, Ding; Zou, Weiwei; et al. (Frontiers in Endocrinology, 2025)
BackgroundMitochondrial dysfunction in immature oocytes remains a critical barrier to successful in vitro maturation (IVM), particularly in cases of diminished ovarian reserve. While NAD+ precursors are extensively studied, the direct impact of NADH - the reduced form central to electron transport - on human oocyte maturation remains unexplored.MethodsDiscarded GV/MⅠ oocytes from controlled ovarian hyperstimulation (COH) cycles were randomized to IVM media supplemented with NADH (10-8-10–4 M). The optimal concentration (10–6 M) was determined by embryonic development. Mechanistic analyses included: mitochondrial phenotyping, single-cell RNA sequencing (scRNA-seq) and intervention experiments.ResultsNADH boosted maturation rates by 26.31% and blastocyst rates by 23.4% versus controls. Mitochondrial indices surged (ATP, mitochondrial membrane potential, glutathione, all P < 0.05), accompanied by ROS reduction. scRNA-seq and immunofluorescence results revealed NADH upregulated CDK2 and GAS6 genes. CDK2 inhibition suppressed maturation (5.13%), while NADH co-treatment partially restored rates (34.21%) after 24 hours. Exogenous GAS6 enhanced blastocyst formation by 44.44%.ConclusionThis pilot study demonstrates that NADH, as a mitochondrial bioenergetic enhancer, ameliorates Human oocytes maturation and subsequent embryonic development, with this promotive effect appearing to be associated with upregulation of CDK2 and GAS6.